483 Neuroanatomical and Neurofunctional Correlates of Unexplained Excessive Daytime Sleepiness. (3rd May 2021) - Cook, Jesse; Plante, David
Abstract: Introduction: Excessive daytime sleepiness (EDS) frequently presents as a secondary symptom, but some experience EDS in the absence of an explanatory medical condition, psychiatric illness, sleep disorder, or medication/substance use. The neurobiology underlying unexplained EDS (uEDS) is poorly understood, which contributes to the existing limitations in uEDS classification, assessment, and treatment. This investigation was designed to identify potential neuroanatomical and neurofunctional correlates of uEDS. Methods: Data were acquired from the open-access Stockholm Sleepy Brain (SSB) Project, which included either young (20–30 years old) or older (65–75 years old) adults. SSB criteria ruled out common EDS explanations. A uEDS sample (N = 18; Percentage Female = 33%; Percentage Young = 33%) was established using Epworth Sleepiness Scale (ESS) ≥ 11. Age-and-sex matched controls without EDS (noEDS) were identified. T1-weighted MRI and resting-state fMRI (rs-fMRI) data were compiled for each subject, as well as depression, anxiety, and global health self-ratings. Processing pipelines were performed on T1-weighted and rs-fMRI data. Neuroanatomical analyses compared groups using voxel-based morphometry and across gray matter (GM), white matter (WM), and cerebral spinal fluid volume. Threshold free cluster enhancement was used across all neuroanatomical comparisons. For neurofunctional analyses, seed-based connectivity analysis was performed with a seed placed in the left hemisphere of the medial prefrontal cortex (MNI coordinates: 2 -46 12). Fischer Z-transformed functional connectivity maps were compared across groups. Depression, anxiety, and global health scores were included as covariates and corrections were applied for multiple comparisons, across all analyses. Results: Group characteristics were comparable, except for ESS. Significantly increased GM volume (middle occipital gyrus and precuneus) was associated with uEDS, relative to noEDS. Robust, bilateral increases in WM matter (thalamus, cerebellum, and middle frontal gyrus) were observed for uEDS, relative to noEDS. No significant group differences were observed in rs-fMRI. Conclusion: Significant neuroanatomical alterations were associated with uEDS that included increases in both GM and WM. These findings converge on previous research associating anatomical differences within the default mode network with uEDS. Future research using more sensitive quantitative measures of WM is warranted. Support (if any): This project was supported by a National Institute Nursing Research grant (NR018288).